Simulation of the performance of phased-array transducer - Lean, Hui Qi (2017)
Using an established algorithm, a modeled phased array HIFU transducer was evaluated. The regularly spaced array was evaluated on the shifting of a single focus in the transverse and axial direction from the geometric focal point, and the shifting of the multi-foci in the transverse direction while retaining the same center coordinates. Relations between the peak pressure at focus and grating lobe, and the area of focus and grating lobe against the shift in the respective axis was found and discussed. The phased array HIFU transducer was found to be capable of shifting a safe steering distance of +1.1 cm in the transverse direction, between -3 cm and +0.5 cm in the axial direction from the geometric focus of (0, 0, 10) cm and a +0.4 cm multi-foci shift in the lateral direction.